Regulation of stress-induced hematopoiesis. Issue 4 (July 2015) - Zhao, Jimmy L.; Baltimore, David
Abstract : Purpose of review: Hematopoietic stem cells can self-renew and also give rise to the entire repertoire of hematopoietic cells. During acute infectious and inflammatory stresses, the hematopoietic system can quickly adapt to demand by increasing output of innate immune cells many-fold, often at the expense of lymphopoiesis and erythropoiesis. We review recent advances in understanding the regulation of stress-induced hematopoiesis with a specific focus on the direct effects of inflammatory signaling on hematopoietic stem and progenitor cells (HSPCs). Recent findings: Recent studies have highlighted several areas of exciting new developments in the field, including the complex interaction and crosstalk within HSPCs and between bone marrow mesenchymal stem cells and endothelial cells needed to achieve regulated myelopoiesis, identification of increased number of inflammatory and infectious molecules with direct effects on HSPCs, the critical role of inflammatory signaling on embryonic specification of hematopoietic stem cells, and the ability of cytokines to instruct lineage choice at the HSPC level. Summary: These exciting new findings will shape our fundamental understanding of how inflammatory signaling regulates hematopoiesis in health and disease, and facilitate the development of potential interventions to treat hematologic diseases associated with altered inflammatory signaling.